Phishing Detection Applications for Website and Domain at Browser using Virustototal API - Wellson Leewando; Javier Paulus; Valentino Nooril; Nadia Nadia (Bina Nusantara University, 2023)
The purpose of this research is to create a browser extension-based application that can detect malicious sites to minimize phishing attacks. The research method used is to conduct a literature study and collect data from the questionnaire results. Research testing methods are blackbox testing, performance testing using 100 URL with precision and recall method, and comparison between two other simillar applications. The results of this study indicate that this application has good functionality and can reduce phishing attacks on users. The conclusion that can be drawn from this research is that the malicious site detection feature in browser extensions can enhance user protection from phishing attacks